2020
DOI: 10.1093/mnras/staa355
|View full text |Cite
|
Sign up to set email alerts
|

The redshift evolution of rest-UV spectroscopic properties to z ∼ 5

Abstract: We perform a comprehensive analysis of the redshift evolution of the rest-UV spectra of star-forming galaxies out to z ∼ 5. We combine new z ∼ 5 measurements of HI Lyα and low-and high-ionization interstellar metal absorption features with comparable measurements at z ∼ 2-4. This redshift range covers the peak epoch of star formation in the Universe and extends back towards the epoch of reionization. We measure the equivalent widths of interstellar absorption features using stacked spectra in bins of Lyα equiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 85 publications
15
28
0
Order By: Relevance
“…Accordingly, f c varies between zero and one and the 'holes' are free of both H I and dust. This model is consistent with correlations found between Lyα emission strength and lowionization interstellar absorption strength in star-forming galaxies at intermediate redshifts (Shapley et al 2003;Steidel et al 2010;Du et al 2018;Pahl et al 2020). S18 defines the attenuated observed spectrum as…”
Section: F Esc Abssupporting
confidence: 91%
“…Accordingly, f c varies between zero and one and the 'holes' are free of both H I and dust. This model is consistent with correlations found between Lyα emission strength and lowionization interstellar absorption strength in star-forming galaxies at intermediate redshifts (Shapley et al 2003;Steidel et al 2010;Du et al 2018;Pahl et al 2020). S18 defines the attenuated observed spectrum as…”
Section: F Esc Abssupporting
confidence: 91%
“…Most importantly, all the samples that we used as comparison at lower redshift (Shapley et al 2003;Steidel et al 2010;Talia et al 2017;Marchi et al 2019) also mainly include mainsequence galaxies that largely overlap in stellar mass with our sample, with differences in SFR and M FUV that are compatible with the evolving main-sequence from z ∼ 2 to z ∼ 5. In particular, at z ∼ 2.3, the sample in Steidel et al (2010) covers masses 10 9 < M * < 10 11 M , 10 < SFR < 100 M yr −1 , and far-UV absolute magnitudes −22.5 < M FUV < −19.7 (see Erb et al 2006a,b), with ranges that are very similar to those reported by Du et al (2018) and Pahl et al (2020). The 800 galaxies at z ∼ 3 that are stacked in Shapley et al (2003) have −22.6 < M FUV < −20.3, with an average M FUV ∼ −21.4, and have SFRs 25 < SFR < 50 M yr −1 .…”
Section: Associated Optical/nir and Other Multiwavelength Datasupporting
confidence: 66%
“…However, we note that only in galaxies with the smallest ∆v Lyα might the red peak be appreciably reduced (and possibly shifted by the ISM absorption to redder wavelengths): in these 20% of the cases, it is possible in principle that we underestimate the Lyα flux and overestimate the ∆v Lyα (although it is unlikely that this is a systematic effect: these galaxies are already the galaxies with the largest f esc (Lyα) and the smallest ∆v Lyα ). Pahl et al (2020) have shown that the red peak in a composite of ∼200 z ∼ 5 galaxies is only marginally affected by the IGM absorption.…”
Section: Spectroscopic Data and Measurementsmentioning
confidence: 99%
“…Other sources can have a very bright Lyman α line, which has a lot of weight in the determination of the redshift. While [CII] traces the gas in the galaxy and is very close to the systemic velocity, Lyman α radiative transfer is complex and can produce significant offsets (e.g., Steidel et al 2010;Faisst et al 2016;Matthee et al 2017Matthee et al , 2019Carniani et al 2018b;Verhamme et al 2018;Pahl et al 2020;Behrens et al 2019). A complete analysis of the origins of these offsets is presented in Faisst et al (2020).…”
Section: Offsets Between Optical and [Cii] Redshiftsmentioning
confidence: 99%